Mucinous adenocarcinoma of gall bladder: a case report - Tangde, Ashwini Radhakishan; Rathod, Santosh Govind; Joshi, Anil R.; Bindu, Rajan S. (International Journal of Research in Medical Sciences, 2017)
Gall bladder carcinoma is the fifth most common malignancy of gastrointestinal tract. Mucinous carcinoma of gall bladder is very rare variant of gall bladder carcinoma. Only 20 cases of mucinous carcinoma reported till now. We report one such case of 55yr old female patient presented to our hospital with complaining of pain in right hypochondriac region and vomiting since, one month. Radiological examination revealed neoplastic thickening of gall bladder neck with cholelithiasis. Cholecystectomy was performed and specimen showed glistening grey white infiltrative firm solid mass at the neck of gall bladder. On microscopic examination showed mucinous adenocarcinoma. Tumour comprised of cystically dilated mucin filled glands. Tumour was seen infiltrating into muscle layer.